Cervical cancer: Part I human papilloma virus vaccination in Taiwan - Szu-Ting Yang; Peng-Hui Wang; Hung-Hsien Liu; Wen-Hsun Chang; Fang-Wei Chou; Wen-Ling Lee (Taiwanese Journal of Obstetrics & Gynecology, 2024)
A significant decline in both incidence and prevalence of cervical cancers after widespread-introducing cervical screening strategy by Papanicolau test (Pap test) has been found in the world, but cervical cancer is still one of the most common female cancers, reporting the fourth prevalence and also one of the leading causes to result in main women-associated morbidity and mortality, particularly for those women living in low- and middle-income countries. Cervical cancer is one of the most important health concerns directly destroying the global health-care system, partly because of not only increasing the disability either secondary to diseases themselves of victims or mediated by treatment-related adverse events to the survivors but also acting as a leading cause of death of diseased patients worldwide, alarming the urgent need to do something to minimize the catastrophic diseases-related heavy socioeconomic burden. It is fortunate that cervical cancer is a preventable disease, based on its strong association with human papillomavirus (HPV) infection (more than 95%), particularly for those high-risk HPV (HR-HPV) and its high possibility by detecting HPV infection before the development of cervical cancer as well as an effective prevention by HPV vaccination. That is why WHO (World Health Organization) considers cervical cancer as a public problem and attempts to accelerate the elimination of cervical cancer program by three-pillar approach (90:70:90% targets), including (1) 90% of girls are fully vaccinated with HPV vaccine by 15 years of age; (2) 70% of women are screened with a high-performance test by 35 and 45 years of age and precancerous lesions are treated early; and (3) 90% of women identified with cervical diseases receive appropriate and adequate treatment. Herein, this review focuses on the HPV vaccination as Part I, including global recommendations and Taiwan government's policy for HPV vaccination.